Positive plate, preparation method thereof and battery
By adopting the positive active active layer and carbon set flow of the porous structure in the positive film, the problem of low existing ion transmission efficiency of ionic ionic ion is solved, and the battery multiplier performance and production efficiency are improved. At the same time, the cycle stability of the battery is improved. And security.
Patent Information
- Application Number
- CN202411480246.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing positive electrode sheet has the problem of low ion transmission efficiency, which limits the battery's rate performance.
The positive active layer with a porous structure with a porous structure is adopted. The positive active layer is composed of positive active materials and carbon layers covered with the surface of its surface. The average pore diameter is controlled at 0.2 to 1 μm, and the pore rate is controlled at 10-40 %.
By optimizing the structure of the positive activity layer, the migration rate of ions and the infiltration rate of electrolytes are improved, the battery's multiplier performance and production efficiency are improved, and the cycle stability and safety of the battery are enhanced.
Smart Images

Figure CN119361603A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode sheet and a preparation method thereof, and a battery. Background Art
[0002] The positive electrode is one of the key factors that determine the electrochemical performance, safety and cost of the battery. In order to promote ion transport and improve the kinetics of electrochemical reactions, designing suitable positive electrode materials and electrode structures is an effective way to reduce the mean free path of ions and electrons and increase the reaction rate. At present, the positive electrode sheet is made by coating a mixed slurry of positive electrode materials, conductive agents and adhesives on a metal foil (current collector), and then drying and rolling to obtain the electrode sheet. The electrode sheet prepared by this process has disordered and distorted ion diffusion channels, which hinders the diffusion of ions and limits the rate performance of the battery. Summary of the invention
[0003] The main purpose of the present invention is to provide a positive electrode sheet and a preparation method thereof, and a battery, so as to solve the problem of low ion transmission efficiency of the positive electrode sheet in the prior art.
[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a positive electrode sheet, comprising a carbon-coated current collector and a positive electrode active layer, wherein the material of the positive electrode active layer comprises a positive electrode active material and a carbon layer coated on the surface of the positive electrode active material, the positive electrode active layer has a porous structure, and its average pore size is 0.2 to 1 μm, and the porosity of the positive electrode active layer is 10 to 40%.
[0005] Controlling the average pore size of the positive electrode active layer within the range of 0.2 to 1 μm and the porosity of the positive electrode active layer within the range of 10 to 40% helps to improve the migration rate of ions and the infiltration rate of the electrolyte while ensuring the structural stability of the positive electrode active layer, thereby helping to improve the rate performance and production efficiency of the battery.
[0006] Furthermore, the thickness of the carbon layer is 1-10 nm; and / or the mass ratio of the positive electrode active material to the carbon layer is 1:0.01-0.05.
[0007] The carbon layer with the above thickness helps to improve the bonding force between the positive electrode active layer and the carbon-coated current collector. The mass ratio of the positive electrode active material to the carbon layer within the above range helps to improve the conductivity and structural stability of the positive electrode active layer.
[0008] Furthermore, the thickness of the above-mentioned positive electrode active layer is 100 to 400 μm; and / or the carbon-coated current collector is a carbon-coated aluminum foil and / or a carbon-coated copper foil; and / or the positive electrode active material is a polyanion positive electrode active material; preferably, the polyanion positive electrode active material is selected from any one or more of phosphate positive electrode active materials, sulfate positive electrode active materials and silicate positive electrode active materials.
[0009] The positive electrode active layer having the above thickness helps to further improve the migration rate of ions and the infiltration rate of the electrolyte. The above type of carbon-coated current collector helps to improve the conductivity of the carbon-coated current collector. The above type of positive electrode active material helps to further improve the energy density of the positive electrode active layer.
[0010] According to another aspect of the present invention, there is provided a method for preparing the aforementioned positive electrode sheet, the method comprising: step S1, mixing various precursor raw materials including positive electrode active materials, a carbon source, a dispersant, a carbonaceous conductive agent and a solvent and then grinding them to obtain a slurry; step S2, pre-cooling the carbon-coated current collector to the solidification point of the slurry or below, coating the slurry on the carbon-coated current collector, and forming a positive electrode sheet preform after the slurry solidifies; step S3, freeze-drying and calcining the positive electrode sheet preform in sequence to obtain a positive electrode sheet; wherein the calcination is carried out in a protective gas.
[0011] The grinding treatment in step S1 helps to improve the uniformity of dispersion between the components; in step S2, when the slurry moves to the low-temperature carbon-coated current collector, a temperature gradient field is formed between the bottom and the top of the slurry, and the solvent at the bottom begins to nucleate and crystallize when the temperature drops to the freezing point, and the solute in the slurry is squeezed by the crystals to form a dense pore wall, and finally forms an array of ice crystals parallel to each other. After the solidified slurry is treated by a freeze dryer, the crystals are sublimated and removed, leaving pores with a directional structure and densified precursor pore walls. During the sintering process, the carbon in the carbon source, dispersant and carbonaceous conductive agent fuses to form a carbon layer, and the carbon layer fuses with the carbon material on the surface of the carbon-coated foil to form a strong interface rivet active substance, so that the positive active layer with a specific pore structure and the carbon-coated current collector are tightly combined to form a positive electrode sheet, avoiding the use of a binder. In the preparation method of the present application, the material synthesis process and the electrode sheet production process are integrated into a one-step process, which greatly improves the production efficiency while improving the electrical performance.
[0012] Furthermore, in the above step S2, the surface temperature of the carbon-coated current collector is 0°C to -50°C, preferably -20°C to -40°C.
[0013] Controlling the surface temperature of the carbon-coated current collector within the above range helps to improve the orderliness of the pore structure of the positive electrode active layer.
[0014] Furthermore, in the above step S2, the vacuum degree of freeze drying is ≤10Pa; and / or the cold trap temperature of freeze drying is ≤-50°C; and / or the drying time of freeze drying is 1 to 24h; and / or the protective gas is selected from any one or more of nitrogen, argon, nitrogen-hydrogen mixture and argon-hydrogen mixture; and / or the heating rate of calcination treatment is 1 to 5°C / min; and / or the temperature of calcination treatment is 300 to 550°C; and / or the holding time of calcination treatment is 5 to 20h.
[0015] Controlling the vacuum degree, cold trap temperature and drying time of freeze drying within the above ranges helps to improve the efficiency of solvent removal. Controlling the type of protective gas within the above range helps to enrich the selectivity of gas types. Controlling the heating rate, temperature and holding time of calcination treatment within the above ranges helps to improve the efficiency of positive electrode active material formation.
[0016] Furthermore, in the above step S1, the grinding process includes coarse grinding and sand grinding in sequence, the rotation speed of the coarse grinding is 100 to 500 rpm; and / or, the time of the coarse grinding is 0.5 to 4 hours; and / or, the rotation speed of the sand grinding is 1000 to 3000 rpm; and / or, the time of the sand grinding is 0.5 to 6 hours.
[0017] Controlling the conditions of the rough grinding treatment within the above range helps to improve the uniformity of dispersion of each component.
[0018] Furthermore, the ratio of the total mass of the precursor raw materials of the above-mentioned positive electrode active materials, the mass of the carbon source, the mass of the dispersant, and the mass of the carbonaceous conductive agent is 28:1.1~2.5:0.1~0.2:0.2; and / or, the ratio of the total mass of the precursor raw materials of the positive electrode active materials, the carbon source, the dispersant and the carbonaceous conductive agent to the volume of the solvent is 2.95~6.04:1kg / L.
[0019] It is preferred to control the total mass of each precursor raw material of the positive electrode active material, the mass of the carbon source, the mass of the dispersant, and the mass ratio of the carbonaceous conductive agent within the above range, which helps to give full play to the synergistic effect between the components, thereby helping to form a carbon layer on the surface of the positive electrode active material. It is preferred to control the total mass ratio of each precursor raw material of the positive electrode active material, the carbon source, the dispersant and the carbonaceous conductive agent to the volume ratio of the solvent within the above range, which helps to improve the dispersibility of each component and control the average pore size and porosity of the positive electrode active layer finally formed.
[0020] Furthermore, the carbon source is selected from any one or more of oxalic acid, ascorbic acid, formaldehyde, acetaldehyde, n-butyraldehyde, lactic acid, citric acid, malic acid, oxalic acid, adipic acid, citric acid, soluble starch, ascorbic acid, sucrose and glucose; and / or the dispersant is selected from any one or more of sodium carboxymethyl cellulose, polyacrylic acid and polycarboxylic acid; and / or the carbonaceous conductive agent is selected from any one or more of carbon black Super P, conductive graphite, carbon nanotubes and graphene; and / or the solvent is selected from any one or more of water, tert-butanol and olefins.
[0021] It is preferred to control the types of carbon source, dispersant and carbonaceous conductive agent within the above range, which helps to improve the synergistic effect between the three, thereby helping to form a carbon layer with a stable structure. It is preferred to control the type of solvent within the above range, which helps to improve the dispersibility of each component and control the average pore size and porosity of the finally formed positive electrode active layer.
[0022] According to another aspect of the present invention, a battery is provided, comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet mentioned above.
[0023] The battery has high cycle stability and rate performance.
[0024] By applying the technical solution of the present invention, the positive electrode active layer of the present application is an orderly arranged porous structure, the existence of which helps to shorten the migration path of ions, thereby helping to promote the infiltration of electrolyte in the pores and the rapid migration of ions. The average pore size of the positive electrode active layer is controlled within the range of 0.2 to 1 μm, and the porosity of the positive electrode active layer is controlled within the range of 10 to 40%, which helps to improve the migration rate of ions and the infiltration rate of electrolyte while ensuring the structural stability of the positive electrode active layer, thereby helping to improve the rate performance and production efficiency of the battery. The presence of the carbon layer in the positive electrode active layer helps to improve the conductivity of the positive electrode active layer, and the carbon layer can serve as a physical protective layer to reduce the risk of side reactions between the positive electrode active material and the electrolyte, thereby helping to improve the cycle stability and safety of the battery. More importantly, the carbon layer is fused with the carbon material on the surface of the carbon-coated current collector to form a strong interface, which helps to improve the bonding force between the positive electrode active layer and the carbon-coated current collector, thereby helping to reduce the risk of the positive electrode active layer falling off or pulverizing during the charge and discharge process, thereby helping to improve the long-term stability and life of the battery. Furthermore, the positive electrode active layer of the present application does not contain a binder, which helps to further reduce the resistance of ion transmission on the one hand, and helps to reduce pollution to the environment on the other hand. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0026] Figure 1 The SEM image of the positive electrode active layer in Example 1 of the present application at a low magnification is shown;
[0027] Figure 2 The SEM image of the positive electrode active layer in Example 1 of the present application at a high magnification is shown. DETAILED DESCRIPTION
[0028] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0029] As analyzed in the background technology of this application, the positive electrode sheet in the prior art has the problem of low ion transmission efficiency. In order to solve the above problem, this application provides a positive electrode sheet and a preparation method thereof, and a battery.
[0030] In a typical embodiment of the present application, a positive electrode sheet is provided, comprising a carbon-coated current collector and a positive electrode active layer, wherein the material of the positive electrode active layer comprises a positive electrode active material and a carbon layer coated on the surface of the positive electrode active material, the positive electrode active layer has a porous structure, and its average pore size is 0.2 to 1 μm, and the porosity of the positive electrode active layer is 10 to 40%.
[0031] The positive electrode active layer of the present application is an orderly arranged porous structure, the presence of which helps to shorten the migration path of ions, thereby helping to promote the infiltration of electrolytes in the pores and the rapid migration of ions. Controlling the average pore size of the positive electrode active layer within the range of 0.2 to 1 μm and the porosity of the positive electrode active layer within the range of 10 to 40% helps to improve the migration rate of ions and the infiltration rate of electrolytes while ensuring the structural stability of the positive electrode active layer, thereby helping to improve the rate performance and production efficiency of the battery. The presence of a carbon layer in the positive electrode active layer helps to improve the conductivity of the positive electrode active layer, and the carbon layer can serve as a physical protective layer to reduce the risk of side reactions between the positive electrode active material and the electrolyte, thereby helping to improve the cycle stability and safety of the battery. More importantly, the carbon layer is fused with the carbon material on the surface of the carbon-coated current collector to form a strong interface, which helps to improve the bonding force between the positive electrode active layer and the carbon-coated current collector, thereby helping to reduce the risk of the positive electrode active layer falling off or pulverizing during the charge and discharge process, thereby helping to improve the long-term stability and life of the battery. Furthermore, the positive electrode active layer of the present application does not contain a binder, which helps to further reduce the resistance of ion transmission on the one hand, and helps to reduce pollution to the environment on the other hand.
[0032] In one embodiment of the present application, the thickness of the carbon layer is 1-10 nm; and / or the mass ratio of the positive electrode active material to the carbon layer is 1:0.01-0.05.
[0033] The thickness of the carbon layer is preferably controlled within the above range, which helps to improve the bonding force between the positive electrode active layer and the carbon-coated current collector. The mass ratio of the positive electrode active material to the carbon layer is preferably controlled within the above range, which helps to improve the conductivity and structural stability of the positive electrode active layer while ensuring that the positive electrode active layer has a high energy density.
[0034] In one embodiment of the present application, the thickness of the above-mentioned positive electrode active layer is 100-400 μm; and / or, the carbon-coated current collector is a carbon-coated aluminum foil and / or a carbon-coated copper foil; and / or, the positive electrode active material is a polyanion positive electrode active material; preferably, the polyanion positive electrode active material is selected from any one or more of phosphate positive electrode active materials, sulfate positive electrode active materials and silicate positive electrode active materials.
[0035] A positive electrode active layer that is too thin is not conducive to improving the porosity of the positive electrode active layer, and a positive electrode active layer that is too thick is not conducive to controlling the pore size of the positive electrode active layer and improving the uniformity of the pore structure. It is preferred to control the thickness of the positive electrode active layer within the above range, which helps to further improve the ion migration rate and the electrolyte infiltration rate by controlling the uniformity of the pore structure and the porosity and average pore size of the positive electrode active layer within a suitable range. It is preferred to control the material of the carbon-coated current collector within the above range, which helps to improve the conductivity of the carbon-coated current collector. It is preferred to control the type of positive electrode active material within the above range, which helps to further improve the energy density of the positive electrode active layer.
[0036] Including but not limited to, the chemical formula of the positive electrode active material is: Na x M y (X a O b ) z Z w , wherein M is selected from any one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Ca, Mg, Al and Nb; X is selected from any one or more of Si, S, P, As, B, Mo, W and Ge; Z is P2O7; 1≤x≤6, 0.3≤y≤4, 1≤a≤4, 4≤b≤15, 0≤z≤4, 0≤w≤2, and optionally, the positive electrode active material is Na3Fe2(SO4)3 and / or Na4Fe3(PO4)2(P2O7), and other types of positive electrode active materials that are more compatible with the battery can also be selected according to actual needs.
[0037] In another typical embodiment of the present application, a method for preparing the aforementioned positive electrode sheet is provided, and the preparation method comprises: step S1, mixing various precursor raw materials including positive electrode active materials, a carbon source, a dispersant, a carbonaceous conductive agent and a solvent, and then grinding them to obtain a slurry; step S2, pre-cooling the carbon-coated current collector to the solidification point of the slurry or below, coating the slurry on the carbon-coated current collector, and forming a positive electrode sheet preform after the slurry solidifies; step S3, freeze-drying and calcining the positive electrode sheet preform in sequence to obtain a positive electrode sheet; wherein the calcination treatment is carried out in a protective gas.
[0038] In step S1, the precursor raw materials, carbon source, dispersant, carbonaceous conductive agent and solvent including the positive electrode active material are mixed and ground, which helps to improve the uniformity of dispersion between the components, thereby obtaining a viscous and uniform slurry; in step S2, when the slurry moves to the low-temperature carbon-coated current collector, a temperature gradient field is formed between the bottom and top of the slurry, and the solvent at the bottom begins to nucleate and crystallize when the temperature drops to the freezing point, and the solute in the slurry is squeezed by the crystals to form dense pore walls. As the temperature continues to drop, the solidified crystals gradually grow toward the surface along the direction of the temperature field, and because of the different nucleation sites, an array of ice crystals parallel to each other is eventually formed. After the solidified slurry is treated with a freeze dryer, the crystals are sublimated and removed, leaving pores with a directional structure and densified precursor pore walls. During the sintering process, the carbon in the carbon source, dispersant and carbonaceous conductive agent fuses together to form a carbon layer, and the carbon layer fuses with the carbon material on the surface of the carbon-coated foil to form a strong interface rivet active material, so that the positive electrode active layer with a specific pore structure and the carbon-coated current collector are tightly combined to form a positive electrode sheet, avoiding the use of a binder. In the preparation method of the present application, the material synthesis process and the electrode sheet production process are integrated into a one-step process, which greatly improves production efficiency while improving electrical performance.
[0039] The types of the precursor raw materials of the positive electrode active material can be selected according to the composition of the positive electrode active material to be finally formed, including but not limited to, the precursor raw materials of the positive electrode active material include a sodium source, a metal source and an anion source.
[0040] Optionally, the sodium source is selected from any one or more of sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium sulfate, sodium hydroxide, sodium formate, sodium citrate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate.
[0041] Optionally, the metal source is selected from any one or more of ferric phosphate, ferric sulfate, ferric chloride, ferric nitrate and ferrous oxalate.
[0042] Optionally, the anion source is selected from any one or more of phosphoric acid, sodium sulfate, sodium silicate and sodium fluoride.
[0043] In one embodiment of the present application, in step S2, a carbon-coated current collector is placed on the surface of a continuously flowing substrate, so that the carbon-coated current collector is in a continuously flowing state, the continuously flowing carbon-coated current collector is pre-cooled to the solidification point of the slurry or below, and the slurry is continuously coated on the continuously flowing carbon-coated current collector using a scraper, and after the slurry solidifies, a positive electrode sheet preform is formed. Preferably, the slit of the scraper is 100 to 400 μm, and the speed of the continuous movement of the carbon-coated current collector is 0.1 to 10 m / min.
[0044] In order to further improve the orderliness and porosity of the pore structure of the positive electrode active layer, in one embodiment of the present application, preferably in the above step S2, the surface of the carbon-coated current collector is 0°C to -50°C, preferably -20°C to -40°C.
[0045] In one embodiment of the present application, in the above-mentioned step S2, the vacuum degree of freeze drying is ≤10Pa; and / or the cold trap temperature of freeze drying is ≤-50°C; and / or the drying time of freeze drying is 1 to 24h; and / or the protective gas is selected from any one or more of nitrogen, argon, nitrogen-hydrogen mixture and argon-hydrogen mixture; and / or the heating rate of calcination treatment is 1 to 5°C / min; and / or the temperature of calcination treatment is 300 to 550°C; and / or the holding time of calcination treatment is 5 to 20h.
[0046] The vacuum degree, cold trap temperature and drying time of freeze drying are preferably controlled within the above ranges, which helps to improve the efficiency of solvent removal. The type of protective gas is preferably controlled within the above range, which helps to enrich the selectivity of gas types. The heating rate, temperature and holding time of calcination treatment are preferably controlled within the above ranges, which helps to improve the efficiency of positive electrode active material formation while avoiding the reaction between protective gas and carbon-coated current collector.
[0047] In order to improve the uniformity of dispersion of each component and thus improve the rate performance of the positive electrode sheet, in one embodiment of the present application, preferably in the above step S1, the grinding treatment includes coarse grinding and sand grinding performed sequentially, and the rotation speed of the coarse grinding is 100 to 500 rpm; and / or, the time of the coarse grinding is 0.5 to 4 h; and / or, the rotation speed of the sand grinding is 1000 to 3000 rpm; and / or, the time of the sand grinding is 0.5 to 6 h.
[0048] In one embodiment of the present application, the ratio of the total mass of the precursor raw materials of the above-mentioned positive electrode active materials, the mass of the carbon source, the mass of the dispersant, and the mass of the carbonaceous conductive agent is 28:1.1~2.5:0.1~0.2:0.2; and / or, the ratio of the total mass of the precursor raw materials of the positive electrode active materials, the carbon source, the dispersant and the carbonaceous conductive agent to the volume of the solvent is 2.95~6.04:1kg / L.
[0049] It is preferred to control the total mass of each precursor raw material of the positive electrode active material, the mass of the carbon source, the mass of the dispersant, and the mass ratio of the carbonaceous conductive agent within the above range, which helps to give full play to the synergistic effect between the components, thereby helping to form a carbon layer on the surface of the positive electrode active material. The presence of the carbon layer helps to improve the conductivity of the positive electrode active layer, and the carbon layer can serve as a physical protective layer to reduce the risk of side reactions between the positive electrode active material and the electrolyte, thereby helping to improve the cycle stability and safety of the battery. More importantly, the carbon layer is fused with the carbon material on the surface of the carbon-coated current collector to form a strong interface, which helps to improve the bonding force between the positive electrode active layer and the carbon-coated current collector, thereby helping to reduce the risk of the positive electrode active layer falling off or pulverizing during the charge and discharge process, thereby helping to improve the long-term stability and life of the battery. It is preferred to control the total mass of each precursor raw material of the positive electrode active material, the carbon source, the dispersant and the carbonaceous conductive agent to the volume ratio of the solvent within the above range, which helps to improve the dispersibility of each component and control the average pore size and porosity of the positive electrode active layer finally formed.
[0050] In one embodiment of the present application, the carbon source is selected from any one or more of oxalic acid, ascorbic acid, formaldehyde, acetaldehyde, n-butyraldehyde, lactic acid, citric acid, malic acid, oxalic acid, adipic acid, citric acid, soluble starch, ascorbic acid, sucrose and glucose; and / or the dispersant is selected from any one or more of sodium carboxymethyl cellulose, polyacrylic acid and polycarboxylic acid; and / or the carbonaceous conductive agent is selected from any one or more of carbon black Super P, conductive graphite, carbon nanotubes and graphene; and / or the solvent is selected from any one or more of water, tert-butanol and olefins.
[0051] It is preferred to control the types of carbon source, dispersant and carbonaceous conductive agent within the above range, which helps to improve the synergistic effect between the three, thereby helping to form a carbon layer with a stable structure. It is preferred to control the type of solvent within the above range, which helps to improve the dispersibility of each component and control the average pore size and porosity of the final positive electrode active layer. Different solvents have different freezing points, and the freezing point can be adjusted by mixing solvents, and can be adapted to aqueous and organic dispersion systems.
[0052] In another typical embodiment of the present application, a battery is provided, including a positive electrode sheet, an electrolyte and a negative electrode sheet, and the positive electrode sheet is the positive electrode sheet mentioned above.
[0053] Since the battery has the positive electrode sheet of the present application, the battery has higher cycle stability and rate performance.
[0054] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0055] Example 1
[0056] Take 28kg of ferric phosphate, sodium carbonate and phosphoric acid according to the molar ratio of Na:Fe:P of 4:3:4, add 1.6kg of glucose, 0.2kg of sodium carboxymethyl cellulose and 0.2kg of carbonaceous conductive agent carbon black Super P into 10L water and stir evenly, then transfer to the coarse grinder and sand mill in turn, coarse grind at 100rpm for 4h and sand grind at 1000rpm for 6h to obtain a viscous and uniform precursor slurry. Carbon-coated aluminum foil is placed on the surface of the base tape as a carrier film, and a temperature control device is embedded in the bottom of the base tape to cool the surface temperature of the carbon-coated aluminum foil to -20℃ and move at a speed of 1m / min. The precursor slurry is transferred to the slurry box of the casting machine and evenly coated on the surface of the carbon-coated aluminum foil through a 200μm scraper slit. After the slurry is frozen, it is transferred to a freeze dryer, the vacuum degree is set to 10Pa, the cold trap temperature is set to -50℃, and dried for 6h. The dried sample was placed in a nitrogen atmosphere, heated to 500°C at a rate of 2°C / min for calcination, and maintained for 10 hours to obtain a positive electrode sheet, wherein the thickness of the positive electrode active layer in the positive electrode sheet is 200μm, the positive electrode active material in the positive electrode active layer is Na4Fe3(PO4)2(P2O7), the thickness of the carbon layer coated on the surface of the positive electrode active material is 3nm, and the mass ratio of the positive electrode active material to the carbon layer is 1:0.02.
[0057] Example 2
[0058] The difference from Example 1 is that the mass of glucose is 1.9 kg, the mass of sodium carboxymethyl cellulose is 0.1 kg, the mass of carbonaceous conductive agent carbon black Super P is 0.2 kg, the volume of water is 5 L, and finally a positive electrode sheet is obtained. The thickness of the carbon layer coated on the surface of the positive electrode active material is 5 nm, and the mass ratio of the positive electrode active material to the carbon layer is 1:0.025.
[0059] Example 3
[0060] The difference from Example 1 is that the slit of the scraper is 400 μm, and the positive electrode sheet finally obtained has a thickness of 400 μm for the positive electrode active layer.
[0061] Example 4
[0062] The difference from Example 1 is that the moving speed of the carbon-coated aluminum foil is 5 m / min, and the positive electrode sheet is finally obtained.
[0063] Example 5
[0064] The difference from Example 1 is that the surface temperature of the carbon-coated aluminum foil is -40°C, and a positive electrode sheet is finally obtained.
[0065] Example 6
[0066] Take 28kg of ferric phosphate and sodium sulfate according to the molar ratio of Na:Fe:S of 2:1:2, add it with 1.6kg of glucose, 0.2kg of polyacrylic acid, and 0.2kg of carbonaceous conductive agent carbon black Super P into 10L water and stir evenly, then transfer to the coarse grinder and sand mill in turn, coarse grind at 100rpm for 2h, and sand grind at 2000rpm for 4h to obtain a viscous and uniform precursor slurry. Carbon-coated aluminum foil is placed on the surface of the base tape as a carrier film, and a temperature control device is embedded in the bottom of the base tape to cool the surface temperature of the carbon-coated aluminum foil to -20℃ and move at a speed of 1m / min. The precursor slurry is transferred to the slurry box of the casting machine and evenly coated on the surface of the carbon-coated aluminum foil through a 200μm scraper slit. After the slurry is frozen, it is transferred to a freeze dryer, the vacuum degree is set to 10Pa, the cold trap temperature is set to -50℃, and dried for 6h. The dried sample was placed in a nitrogen atmosphere, heated to 350°C at a rate of 2°C / min for calcination, and maintained for 10 hours to obtain a positive electrode sheet, wherein the thickness of the positive electrode active layer in the positive electrode sheet is 200μm, the positive electrode active material in the positive electrode active layer is Na3Fe2(SO4)3, the thickness of the carbon layer coated on the surface of the positive electrode active material is 3.5nm, and the mass ratio of the positive electrode active material to the carbon layer is 1:0.022.
[0067] Example 7
[0068] The difference from Example 1 is that the mass of glucose is 1.1 kg, the mass of sodium carboxymethyl cellulose is 0.2 kg, and the mass of carbonaceous conductive agent carbon black Super P is 0.2 kg. Finally, a positive electrode sheet is obtained, the thickness of the carbon layer coated on the surface of the positive electrode active material is 1 nm, and the mass ratio of the positive electrode active material to the carbon layer is 1:0.01.
[0069] Example 8
[0070] The difference from Example 1 is that the mass of glucose is 2.5 kg, the mass of sodium carboxymethyl cellulose is 0.2 kg, and the mass of carbonaceous conductive agent carbon black Super P is 0.2 kg. Finally, a positive electrode sheet is obtained, the thickness of the carbon layer coated on the surface of the positive electrode active material is 10 nm, and the mass ratio of the positive electrode active material to the carbon layer is 1:0.05.
[0071] Example 9
[0072] The difference from Example 1 is that the mass of glucose is 0.8 kg, the mass of sodium carboxymethyl cellulose is 0.2 kg, and the mass of carbonaceous conductive agent carbon black Super P is 0.2 kg. Finally, a positive electrode sheet is obtained, the thickness of the carbon layer coated on the surface of the positive electrode active material is 0.5 nm, and the mass ratio of the positive electrode active material to the carbon layer is 1:0.008.
[0073] Example 10
[0074] The difference from Example 1 is that the heating rate of the calcination treatment is 2°C / min, the calcination temperature is 600°C, the holding time of the calcination treatment is 5h, and finally a positive electrode sheet is obtained.
[0075] Embodiment 11
[0076] The difference from Example 1 is that the rotation speed of the coarse grinding treatment is 500 rpm, the time of the coarse grinding treatment is 0.5 h, and the rotation speed of the sand grinding treatment is 3000 rpm, and the time of the sand grinding treatment is 0.5 h.
[0077] Example 12
[0078] The difference from Example 1 is that the rotation speed of the coarse grinding treatment is 90 rpm, the time of the coarse grinding treatment is 1 hour, and the rotation speed of the sand grinding treatment is 1500 rpm, and the time of the sand grinding treatment is 3 hours.
[0079] Example 13
[0080] The difference from Example 1 is that the surface temperature of the carbon-coated aluminum foil is -5°C, and a positive electrode sheet is finally obtained.
[0081] Comparative Example 1
[0082] The difference from Example 1 is that the precursor slurry is placed in a 60°C vacuum drying oven for 24 hours. The dried sample is placed in a nitrogen atmosphere, heated to 500°C at 2°C / min, and maintained for 10 hours to obtain a positive electrode material. The positive electrode material is mixed with N-methylpyrrolidone (NMP), polyvinylidene fluoride (PVDF), and carbon black Super P in a mass ratio of 47.5:50:1.25:1.25. The slurry is coated on the surface of the carbon-coated aluminum foil and placed in an oven for drying to obtain a positive electrode sheet.
[0083] Comparative Example 2
[0084] The difference from Example 6 is that the precursor slurry is placed in a 60°C vacuum drying oven for 24 hours. The dried sample is placed in a nitrogen atmosphere, heated to 350°C at 2°C / min, and maintained for 10 hours to obtain a positive electrode material, and the positive electrode material is mixed with N-methylpyrrolidone (NMP), polyvinylidene fluoride (PVDF), and carbon black Super P in a mass ratio of 47.5:50:1.25:1.25. The slurry is coated on the surface of the carbon-coated aluminum foil and placed in an oven for drying to obtain a positive electrode sheet.
[0085] The porosity and average pore size of the positive electrode active layer on the positive electrode sheet prepared in the example were measured. The measurement results are shown in Table 1.
[0086] The positive electrode sheets prepared in the embodiment and the comparative example were assembled into button-type batteries in a glove box with water and oxygen below 0.01 ppm. The discharge capacities at different rates were tested at room temperature. The specific results are shown in Table 1.
[0087] Table 1
[0088]
[0089] According to Table 1, the batteries of Examples 1 to 6 have better rate performance, especially when the current density reaches 10C, the discharge capacity of the embodiments is significantly higher than that of the comparative example. This is because the precursor particles are pushed aside and squeezed to form pore walls under the action of ice crystals growing from bottom to top. After freeze-drying and high-temperature sintering, the precursor particles react to form positive electrode materials, which are melted to form integrated dense pore walls. This oriented pore structure reduces the penetration path of the electrolyte, increases the degree of electrolyte infiltration, reduces the distance of ion transmission, and improves the rate performance of the material. Especially at high rates, the advantages of this oriented structure are more obvious.
[0090] Figure 1 This is a SEM image of the positive electrode active layer in Example 1 of the present application at a low magnification. Figure 1 It can be measured that the positive electrode active layer is an ordered pore structure;
[0091] Figure 2 This is a SEM image of the positive electrode active layer in Example 1 of the present application at a high magnification. Figure 2 It can be seen that the positive electrode active layer is a pore wall formed by the fusion of positive electrode material particles.
[0092] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0093] The positive electrode active layer of the present application is an orderly arranged porous structure, the presence of which helps to shorten the migration path of ions, thereby helping to promote the infiltration of electrolytes in the pores and the rapid migration of ions. Controlling the average pore size of the positive electrode active layer within the range of 0.2 to 1 μm and the porosity of the positive electrode active layer within the range of 10 to 40% helps to improve the migration rate of ions and the infiltration rate of electrolytes while ensuring the structural stability of the positive electrode active layer, thereby helping to improve the rate performance and production efficiency of the battery. The presence of a carbon layer in the positive electrode active layer helps to improve the conductivity of the positive electrode active layer, and the carbon layer can serve as a physical protective layer to reduce the risk of side reactions between the positive electrode active material and the electrolyte, thereby helping to improve the cycle stability and safety of the battery. More importantly, the carbon layer is fused with the carbon material on the surface of the carbon-coated current collector to form a strong interface, which helps to improve the bonding force between the positive electrode active layer and the carbon-coated current collector, thereby helping to reduce the risk of the positive electrode active layer falling off or pulverizing during the charge and discharge process, thereby helping to improve the long-term stability and life of the battery. Furthermore, the positive electrode active layer of the present application does not contain a binder, which helps to further reduce the resistance of ion transmission on the one hand, and helps to reduce pollution to the environment on the other hand.
[0094] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A positive electrode sheet, comprising a carbon-coated current collector and a positive electrode active layer, characterized in that: The material of the positive electrode active layer includes a positive electrode active material and a carbon layer coated on the surface of the positive electrode active material. The positive electrode active layer has a porous structure with an average pore size of 0.2 to 1 μm and a porosity of 10 to 40%.
2. The positive electrode sheet according to claim 1, characterized in that: The thickness of the carbon layer is 1 to 10 nm; and / or the mass ratio of the positive electrode active material to the carbon layer is 1:0.01 to 0.
05.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: The thickness of the positive electrode active layer is 100 to 400 μm; and / or the carbon-coated current collector is a carbon-coated aluminum foil and / or a carbon-coated copper foil; and / or the positive electrode active material is a polyanion positive electrode active material; preferably, the polyanion positive electrode active material is selected from any one or more of phosphate positive electrode active materials, sulfate positive electrode active materials and silicate positive electrode active materials.
4. A method for preparing a positive electrode sheet according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, mixing various precursor raw materials including positive electrode active materials, a carbon source, a dispersant, a carbonaceous conductive agent and a solvent, and then grinding them to obtain a slurry; Step S2, pre-cooling the carbon-coated current collector to the solidification point of the slurry or below, coating the slurry on the carbon-coated current collector, and forming a positive electrode sheet preform after the slurry solidifies; Step S3, freeze-drying and calcining the positive electrode sheet preform in sequence to obtain the positive electrode sheet; wherein the calcination is performed in a protective gas.
5. The preparation method according to claim 4, characterized in that: In the step S2, the surface temperature of the carbon-coated current collector is 0°C to -50°C, preferably -20°C to -40°C.
6. The preparation method according to claim 4 or 5, characterized in that: In the step S2, the vacuum degree of the freeze drying is ≤10Pa; and / or the cold trap temperature of the freeze drying is ≤-50°C; and / or the drying time of the freeze drying is 1 to 24 hours; and / or the protective gas is selected from any one or more of nitrogen, argon, nitrogen-hydrogen mixture and argon-hydrogen mixture; and / or the heating rate of the calcination treatment is 1 to 5°C / min; and / or the temperature of the calcination treatment is 300 to 550°C; and / or the holding time of the calcination treatment is 5 to 20 hours.
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step S1, the grinding process includes a coarse grinding process and a sand grinding process performed sequentially, the rotation speed of the coarse grinding process is 100 to 500 rpm; and / or, the time of the coarse grinding process is 0.5 to 4 hours; and / or, the rotation speed of the sand grinding process is 1000 to 3000 rpm; and / or, the time of the sand grinding process is 0.5 to 6 hours.
8. The preparation method according to any one of claims 4 to 7, characterized in that The ratio of the total mass of the precursor raw materials of the positive electrode active material, the mass of the carbon source, the mass of the dispersant, and the mass of the carbonaceous conductive agent is 28: 1.1-2.5:0.1-0.2:0.2; and / or, the ratio of the total mass of the precursor raw materials of the positive electrode active material, the carbon source, the dispersant and the carbonaceous conductive agent to the volume of the solvent is 2.95-6.04:1 kg / L.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The carbon source is selected from any one or more of oxalic acid, ascorbic acid, formaldehyde, acetaldehyde, n-butyraldehyde, lactic acid, citric acid, malic acid, oxalic acid, adipic acid, citric acid, soluble starch, ascorbic acid, sucrose and glucose; And / or, the dispersant is selected from any one or more of sodium carboxymethyl cellulose, polyacrylic acid and polycarboxylic acid; And / or, the carbonaceous conductive agent is selected from any one or more of carbon black Super P, conductive graphite, carbon nanotubes and graphene; And / or, the solvent is selected from any one or more of water, tert-butyl alcohol and olefins.
10. A battery comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, characterized in that: The positive electrode sheet is the positive electrode sheet according to any one of claims 1 to 3.
Citation Information
Patent Citations
Positive electrode piece of lithium-ion power battery and preparation method thereof
CN103515616A
Positive plate, battery and preparation method of positive plate
CN114284462A
Lithium ion battery electrode plate and preparation method thereof
CN115440931A
Negative plate, preparation method thereof and lithium iron phosphate battery
CN115440932A
Manufacturing method of positive pole piece of lithium battery
CN116864630A
Cited By
Positive plate and application thereof
CN122511837A